Anesthetic Management and Considerations for Cesarean Delivery in a Patient With Cystic Fibrosis - Richard Pham; Chris Mehdizadeh; Christopher Baker; Leonard J. Soloniuk; Ioana Pasca; Ashish Sinha (Case Reports in Anesthesiology)
Recent advancements in therapeutics and risk reduction in the management of cystic fibrosis have increased the life expectancy of cystic fibrosis patients to the fifth decade of life. As the life expectancy of cystic fibrosis patients has increased, more cystic fibrosis patients have opted to pursue pregnancy. Normal pregnancy is accompanied by physiological changes that affect anesthetic management. These normal physiological changes, combined with the pathological manifestations of cystic fibrosis, create a unique set of anesthetic challenges. Here, we report on the management and clinical course of a 37-year-old parturient with cystic fibrosis, focusing on the anesthetic approach.